Naringin Effectively Protects Cardiomyocytes Against Hypoxia/Reoxygenation Injury - Thi Thu, Vu; Yen, Ngo Thi Hai (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 3, 2021)
This study was conducted to evaluate the protective effect of Naringin (NAR) on H9C2 cardiomyocytes in hypoxia/reoxygenation (HR) injury in vitro induced by the hypoxia chamber. Methods: H9C2 cells were grown under normal (control) and HR conditions. The viability, cardiolipin content and mitochondrial membrane potential of H9C2 cells in experimental groups were analyzed by using suitable kits. Results: The obtained results showed that the addition of Naringin (16÷160 µM) significantly increased the survival rate of H9C2 cells under HR conditions. In particular, NAR had the highest efficiency in preserving mitochondrial function at concentrations of 80 µM and 160 µM. In HR-exposed H9C2 cell group, the cardiolipin content and mitochondrial membrane potential values of H9C2 cells were decreased sharply with that of control (71,64±1,37% and 68,12±2,78%, p<0,05). Interestingly, mitochondrial cardiolipin contents were signigicantly increased in H9C2 cells post-hypoxic treated wtih NAR at dose of 80 µM 160 µM to 87,76±1,89% and 81,09±1,21%. Additionally, post-hypoxic supplementation of NAR at concentration of 80 µM and 160 µM effectively increased mitochondrial membrane potential values. Conclusion: The obtained results are preliminary data on the effects of NAR in protecting mitochondrial-targeted cardiomyocytes against HR injury.